Hardening protective coatings on niobium alloys, their thermal-cyclic creep and long-term strength - Lopata, L.; Lopata, A.; Kachynska, I.; Rybak, I.; Solovykh, A.; Katerinich, S. (Problems of Tribology, 2026)
A solution to the problem of protecting niobium from high-temperature, highly intensive oxidation is considered. The isothermal and thermocyclic creep and long-term strength characteristics of a niobium alloy with three coating variants are determined at temperatures of 1400–250°C in air. A test methodology for niobium alloys with coatings under simultaneous loads, high temperatures, abrupt thermal cycles, and an oxidizing environment with radiant heating and non-contact cooling by focusing radiant energy is presented, ensuring reliable determination of mechanical properties. A comparison of ultimate strains, creep rates, and durability under isothermal and thermocyclic conditions for the three coating variants is conducted, demonstrating the advantage of a combined plasma-diffusion coating over silicide and borosilicide coatings. Differences in creep and long-term strength characteristics of the three coating variants are demonstrated, which are explained by the nature of crack development in the coating. The transition from single “sharp” cracks in the coating to regular cracks in the diffusion sublayer with rounded tops ensures an increase in the strength and durability of the niobium alloy.